Analysis of Bird Damage Prevention Mechanism for Overhead Transmission Lines. (October 2020) - Xiaopo, Mao; Yaodong, Zhang; Xueming, Zhou; Zhiqiang, Feng; Zeqi, Huang; Xiang, Ren; Tianru, Shi; Jianjin, Fu; Junjie, Huang
Abstract: With the continuous development of the power system, 500kV transmission lines have become the backbone of power grid transmission lines. The construction of a large number of transmission lines is intertwined with the activities of birds. Line failures caused by birds have become the main cause of power system trip accidents. First, it seriously threatens the safe operation of the power system, and its degree of damage is second only to lightning strikes and external damage. Through related research and analysis, the bird damage of 500kV transmission line is mainly caused by three aspects: bird droppings, bird body and bird pecking. This paper analyzes the formation mechanism of bird damage on 500kV transmission lines, and provides some guidance for the corresponding prevention measures for the protection of transmission lines from bird damage.